Global constitutionalism from European and East Asian perspectives / edited by Takao Suami, Anne Peters, Dimitri Vanoverbeke, Mattias Kumm. - Suami, Takao, 1954-; Peters, Anne, 1964-; Vanoverbeke, Dimitri; Kumm, Mattias (Cambridge University Press, 2018)
Global Constitutionalism argues that parts of international law can be understood as being grounded in the rule of law and human rights, and insists that international law can and should be interpreted and progressively developed in the direction of greater respect for and realization of those principles. Global Constitutionalism has been discussed primarily by European scholars. Yet without the engagement of scholars from other parts of the world, the universalist claims underlying Global Constitutionalism ring hollow. This is particularly true with regard to East Asia, where nearly half the world's population and a growing share of global economic and military capacities are located. Are East Asian perspectives on Global Constitutionalism similar to European perspectives? Against the background of current power shifts in international law, this book constitutes the first cross-cultural work on various facets of Global Constitutionalism and elaborates a more nuanced concept that fits our times.